Comparison of viral inactivation methods on the characteristics of extracellular vesicles from SARS‐CoV‐2 infected human lung epithelial cells. Issue 12 (5th December 2022) - Kongsomros, Supasek; Pongsakul, Nutkridta; Panachan, Jirawan; Khowawisetsut, Ladawan; Somkird, Jinjuta; Sangma, Chak; Kanjanapruthipong, Tapanee; Wongtrakoongate, Patompon; Chairoungdua, Arthit; Pattanapanyasat, Kovit; Newburg, David S.; Morrow, Ardythe L.; et al.
Abstract: The interaction of SARS‐CoV‐2 infection with extracellular vesicles (EVs) is of particular interest at the moment. Studying SARS‐CoV‐2 contaminated‐EV isolates in instruments located outside of the biosafety level‐3 (BSL‐3) environment requires knowing how viral inactivation methods affect the structure and function of extracellular vesicles (EVs). Therefore, three common viral inactivation methods, ultraviolet‐C (UVC; 1350 mJ/cm 2 ), β‐propiolactone (BPL; 0.005%), heat (56°C, 45 min) were performed on defined EV particles and their proteins, RNAs, and function. Small EVs were isolated from the supernatant of SARS‐CoV‐2‐infected human lung epithelial Calu‐3 cells by stepwise centrifugation, ultrafiltration and qEV size‐exclusion chromatography. The EV isolates contained SARS‐CoV‐2. UVC, BPL and heat completely abolished SARS‐CoV‐2 infectivity of the contaminated EVs. Particle detection by electron microscopy and nanoparticle tracking was less affected by UVC and BPL than heat treatment. Western blot analysis of EV markers was not affected by any of these three methods. UVC reduced SARS‐CoV‐2 spike detectability by quantitative RT‐PCR and slightly altered EV‐derived β‐actin detection. Fibroblast migration‐wound healing activity of the SARS‐CoV‐2 contaminated‐EV isolate was only retained after UVC treatment. In conclusion, specific viral inactivation methods are compatible with specific measures in SARS‐CoV‐2 contaminated‐EV isolates. UVC treatment seems preferable for studying functions of EVs released from SARS‐CoV‐2 infected cells.